Water quality of an integrated crop–livestock system in the northern Great Plains. Issue 1 (27th January 2021) - Faust, D. R.; Liebig, M. A.; Toledo, D.; Archer, D. W.; Kronberg, S. L.; Hendrickson, J. R.; Bawa, Arun; Kumar, S.
Abstract: Impacts of integrated crop–livestock (ICL) systems on water quality have not been well studied. Water quality parameters were quantified for two 30‐min rainfall simulations in wheat ( Triticum aestivum L.)–cover crop, cover crop, and rangeland grass control phases of a long‐term ICL study site in Mandan, ND, in 2017 and 2018. Both pre‐graze and post‐graze simulations were conducted. Nitrate‐N (NO3 − –N), nitrite‐N (NO2 − –N), ammonia‐N (NH4 + –N), phosphate‐P (PO4 3− –P), and total suspended solid (TSS) concentrations and loads were evaluated in surface runoff water, along with concentrations of NO3 − –N, NO2 − –N, NH4 + –N, and PO4 3− –P in infiltration water. Non‐parametric ranked two‐way analysis of variance was used to evaluate differences for vegetation type and grazing as fixed effects, with year as a random effect. Surface runoff concentrations of NO3 − –N and NH4 + –N were significantly different with cover crop and wheat phases being greater than grass. A grazing effect was also observed with pre‐graze significantly greater than post graze for NO2 − –N, NH4 + –N, PO4 3− –P, and TSS surface runoff concentrations. For infiltration water concentrations, similar significant effects of vegetation type were observed for NO3 − –N and PO4 3− –P, while pre‐graze was also greater than post‐graze for NO2 − –N and PO4 3− –P. Due to variable runoff volumes, no significant differences were observed for loads of any parameters. Minimal runoff volumes (0–6.7 L) and significant vegetation and grazing effects in nutrient infiltration water concentrations highlight the importance of infiltration in such studies, particularly at sites in the northern Great Plains.